Identifikasi mikroba Patogen di Mouse Komputer pada Suhu dan Kelembaban Tertentu di Ruang CBT 2 Fakultas Kedokteran Universitas Muhammadiyah Purwokerto - Endah Dwi Astuti; Ratna Wulan Febriyanti; Anis Kusumawati; Paramita Septianawati (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
CBT Room 2 at the Faculty of Medicine, Universitas Muhammadiyah Purwokerto, is used for computer-based lectures and practicums, which may lead to exposure to pathogenic microorganisms from device surfaces, such as computer mice. This study aims to identify pathogenic bacteria and fungi present on mouse surfaces and to evaluate the influence of room temperature and humidity on microbial growth. A total of 60 mouse samples were tested using Nutrient Agar (NA) for bacteria and Sabouraud Dextrose Agar (SDA) for fungi. The recorded room temperature was 25.6°C with a humidity level of 74%. The identification results revealed the presence of Bacillus sp., Escherichia coli, Staphylococcus sp., and Streptococcus sp. on NA media, with Gram-positive bacteria dominating (78.33%). Meanwhile, Aspergillus sp. (40.00%) and Penicillium sp. (38.33%) were found on SDA media. These findings indicate that, although the room's temperature and humidity are not at optimal levels, they still support the growth of mesophilic microbes. The implications suggest the need for routine sterilization efforts to prevent cross-infection risks in the learning environment.